Situation Report: Czechoslovakia, 30 April 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CPCS CC Plenum: Social Security Benefits for the Elderly Improved Anti-Dubcek Campaign Electric Power Shortage A New Phase in the Campaign to Inculcate Atheism Foreign Relations